Application Prototype Attendance System Garuda Indonesia's Premium Service Assistant Employees Use The Waterfall Model - Devy Ferdiansyah; Arief Satriansyah; Jery Rinaldo (Journal of Computer Networks, Architecture and High Performance Computing, 2022)
In the era of information technology which has developed rapidly, it becomes a challenge for users of information technology and encourages every activity of the organization to be able to use it as a support for work activities so as to produce fast and accurate information. PT Garuda Indonesia Tbk as a company engaged in commercial air transportation services that requires good management in employee attendance, special data collection needed to record attendance that can be well organized. The employee attendance process still uses the manual method even though it has been assisted by existing technology, namely using WhatsApp group media every day with a predetermined format and making chat results that have been carried out without a report recap for one month which risks losing attendance data and failures that have occurred. can harm the company. Based on these problems, an attendance system application prototype was made in order to minimize errors. The research method used includes observation, interviews, and literature study. While the system development method using the Waterfall model includes analysis, design, manufacture, testing and system maintenance. The prototype system application that will be developed is expected to be able to build this attendance system more quickly and precisely.